WELFARE REGIMES AND IMMIGRATION CONTROL POLICIES: Canada and Sweden in comparative perspective - Paul,Nathan (2012)
Existing immigration policy research often fails to recognise the analytical distinctions between two distinct, yet related, components of immigration policy: immigration control (IC), and immigrant integration. As a consequence research theorising the sources and outcomes of immigration policy either conflates these two components, or fails to address IC policy in its own right. Where IC policy is addressed the research tends to focus on the actors and institutions that play a role in policy development. Significantly less theoretical attention has been paid to the sources of IC policy content. To address this theoretical gap this study investigates the links connecting welfare regimes with the content of IC policy. Using Esping-Andersen's Three Worlds of Welfare Capitalism as its point of departure, this study hypothesises that the content of immigration control policy mirrors the overarching characteristics that comprise a country's welfare state regime. Similarly, using Canada and Sweden as exemplars of the liberal and social-democratic welfare regime types, this study posits that the content of their respective labour migration regimes (as a subset of general IC policy) will reflect and reinforce both the de-commodification and stratification effects found within their extant welfare regimes. By identifying the specific features of welfare state polices that are repeated within their labour migration systems, this study demonstrates that in both the Canadian and Swedish contexts IC policy is heavily influenced by the content of welfare state policies. These findings provide a more complete understanding of the sources of IC policy. Simultaneously they help explain why nations with many seeming similarities may, nevertheless, implement very different IC regimes. Word Count: 19,890
Keywords: Sweden; Canada; Welfare Regimes; Immigration Control